PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI SISTEM GERAK PADA MANUSIA KELAS VIII SMP ISLAM KEPENUHAN TAHUN PEMBELAJARAN 2014/2015 - Astuti, Sri; Afifah, Nurul; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of the study was to determine the effect of cooperative learning type of talking stick toward biological studentâs learning result on the human moving system at grade VIII of SMP Islam Kepenuhan for academic years on 2014/2015. The method of this study was quasi experiment with nonequivalent control group design type. The sample was taken by using non random sampling. The sample was students as experiment class at grade VIIIA and students as a control class at grade VIII B. The instrument of the study was the test. The data analysis used ttest, and obtained ttest= 8,734 of significant 0,05 that ttable = 1,998, so it can be concluded that by ttest > ttable means that alternative hypothesis was accepted.